2021
DOI: 10.1101/2021.03.19.436132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-REM sleep in major depressive disorder

Abstract: Disturbed sleep is a key symptom in major depressive disorder (MDD). REM sleep alterations are well described in the current literature, but little is known about non-REM sleep alterations. Additionally, sleep disturbances relate to a variety of cognitive symptoms in MDD, but which features of non-REM sleep EEG contribute to this, remains unknown. We comprehensively analyzed non-REM sleep EEG features in three independently collected datasets (N=284). These included MDD patients with a broad age range, varying… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Intriguingly, whereas some polysomnographic studies have confirmed subjective sleep complaints of the patients by reporting decreased slow-wave and delta amplitudes, higher spindle amplitude, lower spindle density, and a more dispersed slow-wave-spindle coupling, others have suggested that oscillatory changes in MDD might be more subtle ( 5 , 6 ). One of the possible explanations for the divergent oscillatory findings is the confounding effect of aperiodic (i.e., non-oscillatory, scale-free) activity ( 7 , 8 , 9 ).…”
mentioning
confidence: 99%
“…Intriguingly, whereas some polysomnographic studies have confirmed subjective sleep complaints of the patients by reporting decreased slow-wave and delta amplitudes, higher spindle amplitude, lower spindle density, and a more dispersed slow-wave-spindle coupling, others have suggested that oscillatory changes in MDD might be more subtle ( 5 , 6 ). One of the possible explanations for the divergent oscillatory findings is the confounding effect of aperiodic (i.e., non-oscillatory, scale-free) activity ( 7 , 8 , 9 ).…”
mentioning
confidence: 99%
“…Finally, it is important to note that in our previous study, we could not detect differences in the total (i.e., non-differentiated to its components) spectral power between unmedicated patients and controls (5). Taken together our recent and current reports demonstrate that in unmedicated patients with MDD, impaired sleep might be related to altered aperiodic activity specifically.…”
Section: Discussionmentioning
confidence: 55%
“…The demographic, clinical, and sleep characteristics of the participants are reported in our previous paper, where this dataset is referred to as “Dataset B” (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations